Essays on technology, trade and labour markets - Stapleton, K (2020)
This thesis consists of three standalone chapters. Chapter 1 investigates how automation in high-income countries affects trade and multinational activity involving less developed ones. This chapter studies Spain's manufacturing sector from 1990 to 2016 and exploits advances in the capabilities of robots over time, finding that the use of robots in Spanish firms actually had a positive impact on their imports from, and number of affiliates in, less developed countries. We provide a modelling framework and empirical analysis on why this has been the case. Chapter 2 explores how trade policy uncertainty and the threat of a reversal of deep integration affects labour demand. This chapter studies how the the threat of trade barriers caused by the Brexit referendum affected the posting of online job adverts between 2015 and 2019, finding that local labour markets that were more exposed to the threat of services trade barriers experienced a relative decline in online job adverts after the referendum, particularly in months when there was heightened uncertainty about trade policy, but the threat of tariffs on goods had little impact. Chapter 3 is on a similar theme to Chapter 1 and explores how the use of Artificial Intelligence (AI) in high income countries affects services offshoring to less developed countries. I construct new measures of the demand for Machine Learning (ML) skills in the UK based upon the text of online job adverts. Using these measures and instrumenting for ML demand using advances in task-specific capabilities of AI over time, I show that the deployment of ML in the UK has had a positive impact on services offshoring, particularly to low and middle income countries.